A book as an attribute of everyday life culture (based on the German classics) - N. N. Misyurov (Библиосфера, 2019)
The functional role of books (scientific, artistic, philosophical, religious and moralistic) in the public practice of the German Enlightenment is comparable to the significance of such major national concepts as the Lutheran faith and a special German character. The idea of aesthetic education in contemporary historical circumstances and socio-political circumstances actually became the ideology of national self-determination. The book, its semantic «images» as literary reading images enshrined in famous works of German classics, helps better revealing the spiritual content of the era and the human inner world (in typical «hero of time»). Educational book (serious and entertaining) defines the vector of social development in Germany.  German book in its «materiality» belongs to the everyday life culture, reflects the level of development of the book business in Germany and the specificity of the «culture of consumption». Everyday life culture is a holistic «life world» shared «values» and «meanings» perceived as a world attitudes and behavioral habits and regarded as a natural space of human activity. Such an approach makes it possible to study the typical, recurring forms of «cultural practices», before remaining on the periphery of classical humanities. «Reading» could be attributed to this range of socio-cultural practices. Philosophical basis of the study is the following: everything that a thing opens our perception is simply «a scheme of sensation» changing in accordance with «angles», in which we perceive them; what the thing is in its materiality can be revealed only through our final experiences. A material thing and its «causality» base in sensory perception of a subject. This series of «material things» should include «the book in general» and specifically German book as an attribute of everyday life culture of the Enlightenment. The author investigates representations of meanings of «books» (ash an abstracted subject of study) realized in the «chronotope» of a literary work. The structure of «reading image» and «book image» identified during the texts analysis of famous masterpieces of German classics have a moral connotation.